Resilience: A Coping Strategy for Physical and Psychological Challenges faced by Chronic Kidney Disease patients - Abeeha Imran, Rubeena Zakar, Ruhma Shahzad, Babar Hussain, Razan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To explore the lived experiences of patients suffering from chronic kidney disease (CKD)to understand how the physical and psychological challenges associated with the disease influenced their life and what role did resilience play to cope up with the physical and psychological challenges. Method: The present study is qualitative in nature and used the phenomenological research design to study the lived experiences of CKD patients. Thirty seven participants were selected through purposive sampling from the nephrology departments of three government hospitals of Lahore which included Jinnah Hospital, Sheikh Zayed Hospital and General Hospital. Data was collected through in-depth interviews. Results: The study revealed that resilience is a major factor which helps to cope up with the physical and psychological challenges associated with CKD by reducing stress, developing a positive self-image, encouraging to fight back, finding alternative treatment options and increasing the will power of CKD patients. Practical implications: Findings of the present study will be helpful for the health care professionals and clinical psychologists to develop strategies and training programs which can increase resilience among patients. Training the patients and care givers regarding how to fight with CKD will lead to an improvement in their quality of life. Conclusion: Resilience enables CKD patients to have a self-worth and brings them back to life by motivating them to participate in the normal activities of life. On the basis of these results, it is expected that this factor can be helpful for the health care professionals, caregivers and patients themselves in order to minimize the negative impacts of the disease through counseling. Keywords: Chronic kidney disease, Resilience, Physical challenges, Psychological challenges